2014
DOI: 10.1016/j.jiph.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C status among health care workers in the five main hospitals in eastern Libya

Abstract: The aim of the present study was to determine the frequency of hepatitis B and C transmission to health care workers (HCWs) in five major hospitals in eastern Libya and to analyze how the risk of these infections are affected by the type of occupation, hospital work place and working period. From July 2008 to June 2009, 601 HCWs (mean age: 32.90 ± 8.85 years) were tested for HBV and HCV markers using ELISA techniques. Polymerase chain reaction (PCR) was performed on all positive samples of HBsAg and Anti-HCV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
(36 reference statements)
2
23
3
Order By: Relevance
“…The characteristics of the wound received by a healthcare worker and the volume of blood transferred are other main factors influencing a possible transmission of HBV or HCV infection. In fact, the devices Elzouki et al [54] 2008 Libya 601 Cross-sectional 12 (2) Alqahtani et al [55] NR Saudi Arabia 300 Cross-sectional 0 Arguillas et al [56] 1990…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the wound received by a healthcare worker and the volume of blood transferred are other main factors influencing a possible transmission of HBV or HCV infection. In fact, the devices Elzouki et al [54] 2008 Libya 601 Cross-sectional 12 (2) Alqahtani et al [55] NR Saudi Arabia 300 Cross-sectional 0 Arguillas et al [56] 1990…”
Section: Resultsmentioning
confidence: 99%
“…Rehman et al [66] , in a small case-control study performed in Pakistan, enrolled 95 healthcare workers and 91 volunteer blood donors as controls and observed higher rates of HBsAg (14% vs 5%) and anti-HBc (36% vs 28%) positivity in the control group. Instead, in a case-control study conducted in Turkey [64] , the rate of HBsAg positivity was similar in 702 healthcare workers and 5670 blood donors (3% vs 2.1%), and in the Philippines, Arguillas et al [56] found 6.5% of 123 healthcare workers and 2.2% of 382 blood donors to be Elzouki et al [54] 2008 Libya 601 Cross-sectional 11 (1.8) 51 (8.5) Alqahtani et al [55] NR Saudi Arabia 300 Cross-sectional 1 (0.3) 25 (8) Arguillas et al [56] 1990…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 97%
See 2 more Smart Citations
“…A study conducted in South Korea with 571 HCWs, reported HBsAg positivity to be 2.4% and anti-HBs positivity 76.9%, and that these rates were not different from that of the general population (20). In another study conducted with 601 HCWs, HBsAg positivity was found 1.8%, and anti-HBs positivity 51.4%; and anti-HBs positivity was identified in laboratory technicians (63.6%), doctors (62.7%), nurses (52%) and cleaning personnel (40%) (21).…”
Section: Discussionmentioning
confidence: 83%